2020
DOI: 10.1002/suco.201900335
|View full text |Cite
|
Sign up to set email alerts
|

Lateral response of ultra‐high performance concrete columns confined with high‐strength spiral stirrups

Abstract: The lateral confinement of stirrups can effectively restrain the unstable lateral expansion of confined concrete and improve the load capacity and the ductility of concrete. The lateral response of stirrups affects the effective confinements on confined concrete and the dilation of core concrete. However, the lateral response of confined concrete has not received enough attention. In this paper, the lateral responses of 24 ultra‐high performance concrete (UHPC) and ultra‐high fiber‐reinforced performance concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Based on the existing literature findings 8,19,21 and the test results, the high‐strength spirals used for confining the RPC could not yield at the peak load. In this case, it was not appropriate to use the yield strength as the basis for the structure calculation.…”
Section: Establishment Of Actual Steel Stress Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the existing literature findings 8,19,21 and the test results, the high‐strength spirals used for confining the RPC could not yield at the peak load. In this case, it was not appropriate to use the yield strength as the basis for the structure calculation.…”
Section: Establishment Of Actual Steel Stress Calculation Methodsmentioning
confidence: 99%
“…Previously, 24 ultra-high-performance concrete (UHPC) and ultra-high-performance fiber-reinforced concrete specimens were tested under axial compression to evaluate the lateral response of stirrups. 8 The work suggested that the mechanism of the confining pressure of stirrups was proved by Poisson effects. For UHPC, Poisson's ratio maintained a specific value in the elastic stage and increased nonlinearly in the plastic stage.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral confinement of stirrups was related to the volumetric ratio, yield strength, spacing, diameter, and configuration 80,81 . The lateral confinement of stirrups can be expressed in Equation (). σle=knormaleρnormalvfyv, where σle was the effective lateral stress of stirrups; knormale was the effective confinement coefficient of stirrups, for rectangular stirrups, knormale=1bi2/6bcorhcor1s/2bcor1s/2hcor/1ρnormals; bi was longitudinal reinforcement spacing confined by stirrups in both directions along the perimeter of the rectangular column section; bcor and hcor were width and height of core concrete; s was the clear spacing of stirrups; ρnormals was the ratio of longitudinal reinforcement.…”
Section: Parametric Analysismentioning
confidence: 99%
“…Mander et al 11,12 developed the efficient confinement concept and proposed evaluation models of efficient confinement coefficients. Saatcioglu et al, 5,8,13 Chang et al, 14,15 and Li 16 found that high‐strength concrete needed more lateral confinements than normal‐strength concrete and improved the tensile strength of stirrups can significantly improve the compressive strength concrete. In particular, Wei and Wu 7 found that the peak stress and the peak strain of concrete (35.8–36.9 MPa) confined with high‐strength steel wire (1803 MPa) was increased by 2.93 and 5.68 times, respectively.…”
Section: Introductionmentioning
confidence: 99%